Variables associated with cortical motor mapping thresholds: A retrospective data review with a unique case of interlimb motor facilitation - Song, Yinchen; Surgenor, James V.; Leeds, Zachary T.; Kanter, John H.; Martinez-Camblor, Pablo; Smith, William J.; Boone, M. Dustin; Abess, Alexander T.; Evans, Linton T.; Kobylarz, Erik J. (Frontiers in Neurology, 2023)
Introduction Intraoperative neuromonitoring (IONM) is crucial to preserve eloquent neurological functions during brain tumor resections. We observed a rare interlimb cortical motor facilitation phenomenon in a patient with recurrent high-grade glioma undergoing craniotomy for tumor resection; the patient’s upper arm motor evoked potentials (MEPs) increased in amplitude significantly (up to 44.52 times larger, p < 0.001) following stimulation of the ipsilateral posterior tibial nerve at 2.79 Hz. With the facilitation effect, the cortical MEP stimulation threshold was reduced by 6 mA to maintain appropriate continuous motor monitoring. It likely has the benefit of reducing the occurrence of stimulation-induced seizures and other adverse events associated with excessive stimulation. Methods We conducted a retrospective data review including 120 patients who underwent brain tumor resection with IONM at our center from 2018 to 2022. A broad range of variables collected pre-and intraoperatively were reviewed. The review aimed to determine: (1) whether we overlooked this facilitation phenomenon in the past, (2) whether this unique finding is related to any specific demographic information, clinical presentation, stimulation parameter (s) or anesthesia management, and (3) whether it is necessary to develop new techniques (such as facilitation methods) to reduce cortical stimulation intensity during intraoperative functional mapping. Results There is no evidence suggesting that clinical presentation, stimulation configuration, or intraoperative anesthesia management of the patient with the facilitation effect were significantly different from our general patient cohort. Even though we did not identify the same facilitation effect in any of these patients, we were able to determine that stimulation thresholds for motor mapping are significantly associated with the location of stimulation (p = 0.003) and the burst suppression ratio (BSR) (p < 0.001). Stimulation-induced seizures, although infrequent (4.05%), could occur unexpectedly even when the BSR was 70%. Discussion We postulated that functional reorganization and neuronal hyperexcitability induced by glioma progression and repeated surgeries were probable underlying mechanisms of the interlimb facilitation phenomenon. Our retrospective review also provided a practical guide to cortical motor mapping in brain tumor patients under general anesthesia. We also underscored the need for developing new techniques to reduce the stimulation intensity and, hence, seizure occurrence.